2021
DOI: 10.3390/su132011421
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Game Analysis on Behavioral Strategies of Government and Residents in Municipal Household Waste Separation

Abstract: Municipal household waste (MHW) separation is a fundamental way to achieve waste reduction and a recycling economy. This study takes the positions of government and residents in MHW separation as the research object, and aims to explore the change process and influencing factors of their decision-making behavior, which is of great significance to attract residents to participate in MHW separation and establish an effective MHW separation mechanism to solve MHW pollution. This paper firstly establishes an evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The government is less sensitive to the penalty for residents. This finding agrees with the result of Wu et al [ 17 ] and is confirmed in reality. Penalty measures have been promoted in some cities where waste separation is mandatory, such as Beijing, Shanghai, and Shenzhen, and fines for residents refusing to separate waste vary.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The government is less sensitive to the penalty for residents. This finding agrees with the result of Wu et al [ 17 ] and is confirmed in reality. Penalty measures have been promoted in some cities where waste separation is mandatory, such as Beijing, Shanghai, and Shenzhen, and fines for residents refusing to separate waste vary.…”
Section: Discussionsupporting
confidence: 94%
“…Zhang [ 57 ] compared the static and dynamic penalty mechanisms for waste separation to analyze the behavioral strategies of the public and the government. Wu et al [ 17 ] established the evolutionary game model involving the government and residents in municipal household waste separation. Based on the prospect theory and evolutionary game, Zhang et al [ 58 ] investigated the behavior change process of government and residents to understand how to optimize the benefits of waste separation for stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lucia et al [ 12 ], Guo et al [ 13 ], Miafodzyeva et al [ 14 ], Convery et al [ 15 ] and Wu [ 16 ] claimed that residents’ household waste classification will be significantly affected by reward and punishment policies, and positive economic incentives are more easily accepted by residents. Wadehra et al [ 17 ] confirmed in the investigation of waste classification in India that the quality of the reward and punishment mechanism is closely related to the implementation effect of the classification policy, and a high-quality reward and punishment mechanism can strengthen the residents’ willingness to classify garbage and promote the residents to implement the behavior of waste classification.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Waste separation (garbage classification) is an upgrade to the traditional waste disposal method and a scientific management method to dispose of urban waste efficiently. “In 2017, the General Office of the State Council of China released the Implementation Plan of Domestic Waste Separation, and 46 cities were identified as pilot cities; from 2019, cities across the country began to fully implement waste-separation policy; by the end of 2025, all cities will have established waste-separation systems” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%